2020
DOI: 10.1038/s41598-020-57856-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of detours in individual human navigation patterns of complex networks

Abstract: Despite its importance for public transportation, communication within organizations or the general understanding of organized knowledge, our understanding of how human individuals navigate complex networked systems is still limited owing to the lack of datasets recording a sufficient amount of navigation paths of individual humans. Here, we analyse 10587 paths recorded from 259 human subjects when navigating between nodes of a complex word-morph network. We find a clear presence of systematic detours organize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Sudarshan Iyengar et al (2012) found that the players' solutions are in average 1.7 times longer than the shortest path between the words. When considering only the solutions of experienced players, the solutions' length even decreases to 1.1-1.2 times the optimal solution length (Gulyás et al 2020).…”
Section: Assumptions Of Centrality Measuresmentioning
confidence: 96%
See 2 more Smart Citations
“…Sudarshan Iyengar et al (2012) found that the players' solutions are in average 1.7 times longer than the shortest path between the words. When considering only the solutions of experienced players, the solutions' length even decreases to 1.1-1.2 times the optimal solution length (Gulyás et al 2020).…”
Section: Assumptions Of Centrality Measuresmentioning
confidence: 96%
“…For the other variant of human navigation in networks where the human themselves travel through the network, there has been a lot of evidence that humans are surprisingly efficient in finding short paths-they are, however, rarely optimal. Sudarshan Iyengar et al (2012) and Gulyás et al (2020) investigated human paths in a word morph game: a player is given two English words, and the player needs to transform the first word into the second word by substituting single letters while intermediate words need to be existing English words. The player's sequence can be seen as a walk through the word network where there is an edge between two existing words if their Hamming distance is exactly one.…”
Section: Assumptions Of Centrality Measuresmentioning
confidence: 99%
See 1 more Smart Citation